On generalized B*-continuity, B*-coverings and B*-separations - Jain, Pankaj; Basu, Chandrani; Panwar, Vivek (Eurasian Mathematical Journal, 2019)
There are various generalizations of continuous functions in topological spaces and B*-continuity is one of them which deals with the Baire property and denseness of the space. We have defined and discussed several properties and interrelations of some further generalizations of B*-continuity, namely, contra B*-continuity, slight B*-continuity and weak B*-continuity. We have also defined certain notions of generalized coverings and separations in terms of B*-sets and studied the effect of generalized B*-continuous functions on spaces having these covering and separation properties.